Accidental poisoning in young children. Issue 1 (March 1982) - Basavaraj, D S; Forster, D P
Abstract : Cases of accidental childhood poisoning admitted to hospital were compared with community controls and hospital controls matched for age and sex. The relative risks of factors in the cases compared with both the control groups were significant for roughness, aggressiveness, noisiness, and pica behaviour in the child, and for large families. Mothers' knowledge of the toxicity of common household products and drugs did not give significant risk differences between cases and controls. The majority of poisonings occurred during the summer months.